(untitled) (Eurasian Journal of Philology Science and Education, 2020)
Oralkhan Bokey dipping into the depth of his era, describing the extraordinary way of life phenomena emphasizes the expressiveness and beauty of the Kazakh language. The writer was presented his works with a wide artistic direction which filled with new philosophical ideas and new artistic thinking, also O.Bokey shows us high skill and a special approach in describing the layered turns of life. The article reveals the paradigm of the author’s image in the Oralkhan Bokey»s novel «Damn bridge», which came to Kazakh prose with an unusual style and revealed its basic writing position. In particular, they examined the features of the manifestation of social and social phenomena, the use of the deictic element in determining the basis of a work, issues of a dualistic worldview, such as good and evil, holiness and deceit. Mastered the author’s ideas and directions of the writer’s work on the holy scripture of Allah, on the goal of creating humanity, on the duty of a person who should not stop loving humanity and live with moral values. The ability to combine symbolic elements and intertext brings him closer to understanding the artistic significance of this event. This work captures the social situation in the society in which he lived, with the help of abstract images such as Shout, That, Echo. Bokey’s spelling style can be recognized as a masterpiece of poetic language. Thus, the writer reveals the general nature of a certain period, time, society, the people around him.